How Efficient Are Hydroponic Lettuce Production Systems in Nutrient Usage Under Low and High Salinity? - Kelsey Vought; Haimanote Bayabil; Ana Martin-Ryals (EDIS, 2025)
This publication aims to highlight the inefficiencies of using a single-rate, EC-based, NFT nutrient dosing practice for lettuce production throughout the growing season. The information contained in this document is relevant to a diverse audience, including students, researchers, Extension agents who have some level of understanding about controlled environment agriculture (CEA) and water and fertilizer management techniques, and hydroponic growers. Written by Kelsey Vought, Haimanote Bayabil, and Ana Martin-Ryals, and published by the UF/IFAS Department of Agricultural and Biological Engineering, February 2025.